THE INFLUENCE OF CREATIVE STYLE PREFERENCE ON CREATIVE BEHAVIOR OF INDONESIA’ CREATIVE INDUSTRY WORKERS - Nugroho J. Setiadi; Regina Inderadi (Bina Nusantara University, 2018)
This study explored the role of creative style preference on employees’ involvement in creative behavior and the moderating effect of creative style preference on the relationship between organisational culture and employees’ creative behavior. The study sample included 128 creative industry workers from 6 small and medium enterprises in Indonesia. Data was collected at Jakarta in early 2018 and gathered by using a questionnaire consisted of 2 cultural behavior dimension to measure workers’ creative behavior, namely presenting creative, concrete and practical ideas and presenting creative suggestions. Questionnaire was using Likert scale and the result was analysed with Exploratory Factor Analysis (EFA) method. The analysis indicted that the two distinct dimensions of creative behavior (presenting creative and practical ideas and presenting creative suggestions) were determined workers’ creative behavior. These two dimensions reflected the level of incremental improvement and presenting radical ideas in their activities. It is concluded that Indonesia’ creative industry workers are creative people who contributed to the productivity of an organization. It is suggested that organisations should create an organizational culture that motivates workers to improve their creativity level.